The problematic aspects of International core crimes and transnational crimes accordingly to International Law //Los aspectos problemáticos de los delitos fundamentales internacionales y los delitos transnacionales de acuerdo con el Derecho Internacional - Shulzhenko, Nadiia; Romashkin, Snizhana; Rubashchenko, Mykola; TatarenkoHаlyna (Revista de la Universidad del Zulia, 2020)
Abstract Today, the boundaries of international crime involving states and transnational organized crime are slowly blurring, and as a result, the number of international crimes is steadily growing. The article analyzes two key groups of crimes: crimes indicated in the Rome Statute and transnational crimes under international conventions. This article is based on the analysis of the main groups of crimes: the first group of international crimes committed with state actors, which includes crimes against humanity, war crimes, crimes of aggression, crimes of genocide; and the second group, crimes committed by criminal groups organized in more than one country with the "international" or "transnational" character of such acts. The authors emphasize the norms of international law, according to which the International Criminal Court, together with international criminal tribunals, have jurisdiction over a small range of key international crimes, including genocide, war crimes and crimes against humanity, aggression, committed by state officials. The main objective of this research is to compare the mechanism for investigating crimes in the jurisdiction of international criminal tribunals and the International Criminal Court, together with the national procedure for investigating transnational crimes, through the ratification of international conventions and the establishment of the International cooperation. The article was made with the following methods: induction, deduction, analogy, as well as historical, dialectical and formal legal methods. Resumen Hoy en día, los límites del crimen internacional que involucra a los estados y el crimen organizado transnacional se están difuminando lentamente y, como resultado, el número de crímenes internacionales está creciendo de manera constante. El artículo analiza dos grupos clave de crímenes: los crímenes indicados en el Estatuto de Roma y los crímenes transnacionales en virtud de las convenciones internacionales. El presente artículo se basa en el análisis de los principales grupos de crímenes: el primer grupo de crímenes internacionales cometidos con actores estatales, que incluye crímenes de lesa humanidad, crímenes de guerra, crímenes de agresión, crímenes de genocidio; y el segundo grupo, crímenes cometidos por grupos delictivos organizados en más de un país con el carácter “internacional” o “transnacional” de tales actos. Los autores enfatizan las normas del derecho internacional, según las cuales la Corte Penal Internacional, junto con los tribunales penales internacionales, tienen jurisdicción sobre una pequeña gama de crímenes internacionales clave, incluidos genocidio, crímenes de guerra y crímenes de lesa humanidad, agresión, cometidos por oficiales de Estado. El objetivo principal de esta investigación es comparar el mecanismo de investigación de crímenes en la jurisdicción de los tribunales penales internacionales y la Corte Penal Internacional, junto con el procedimiento nacional de investigación de crímenes transnacionales, mediante la ratificación de convenios internacionales y el establecimiento de la cooperación internacional. El artículo se realizó con los siguientes métodos: inducción, deducción, analogía, así como métodos jurídicos históricos, dialécticos y formales.